Clinical Features of Ischemic Enteritis Diagnosed by Double-Balloon Endoscopy. (15th April 2021) - Nakamura, Masanao; Yamamura, Takeshi; Maeda, Keiko; Sawada, Tsunaki; Mizutani, Yasuyuki; Ishikawa, Eri; Kakushima, Naomi; Furukawa, Kazuhiro; Ishikawa, Takuya; Ohno, Eizaburo; Honda, Takashi; Kawashima, Hiroki; et al.
Abstract : Introduction . Ischemic enteritis (IE) is a relatively rare small bowel disease that is diagnosed via double-balloon endoscopy (DBE), although the lack of established diagnostic criteria can make it difficult to confirm the diagnosis. This study aimed to describe the clinical characteristics, endoscopic imaging features, and treatments for IE at our center. Patients and Methods . We retrospectively searched the DBE database (1, 521 patients) at Nagoya University Hospital for patients with IE and collected data regarding endoscopic findings, clinical background, and histological findings. The cases were categorized according to whether they involved transient or stenotic IE. Results . The DBE database included 24 patients (14 men) with IE. Transient IE was identified in 9 patients, and stenotic IE was identified in 15. Half of the patients had a history of cerebrovascular and cardiovascular disease. A granular structure at the ulcer base was the most frequently observed DBE finding at the stenotic site. Enterography using the contrast medium revealed that transient IE had a similar stenotic lesion length, relative to stenotic IE, although stenotic IE had a significantly higher stenosis ratio (81% vs. 63%, P = 0.033 ). Small bowel enteroclysis revealed the "lead pipe" sign (11 patients), thumbprinting (3 patients), and the serrated lumen sign (1 patient). Only 1 patient with stenotic IE experienced recurrence after conservative treatment. Conclusion . During DBE, IE was characterized by cannular stenosis with extended and variable ulceration types, which spread over the edge of the stenosis, and a granular appearance at the ulcer base. These findings may help guide the diagnosis of IE.